Analisis Doa Yesus: Studi Patristik Menurut Ignatius Brianchaninov - Refamati Gulo; Hendarto Kusuma (Vieka Wahana Semesta, 2023)
Abstract: Jesus' prayer is centered entirely on His Name and has the power to cast out demons. But it is important to understand that the Prayer of Jesus is not just a formula or a mantra, but a sacred dialogue between the individual and God. Some interpretations and practices of the Jesus Prayer may deviate from Church teaching, so it is important to distinguish true spiritual guidance. Jesus' prayer is not a long or repetitive prayer, but rather a sincere expression of one's desire for mercy, forgiveness, and union with Christ. Jesus' prayer is rooted in Bible verses and requires humility, repentance, and an increasingly intimate relationship with Christ. In practicing the Jesus Prayer, it is important to refer to the wisdom and guidance of the Holy Fathers and seek guidance from spiritual fathers and mothers. Jesus' prayer is relevant today and can be a source of comfort, strength, and spiritual growth for those seeking to embark on a journey of concentration and deep communion with the Lord Jesus Christ. The research method is a review of literature (library reseach) and literature study from the church tradition about the prayer of Jesus, especially based on the writings of St. Ignatius Brianchaninov namely On the Prayer of Jesus which is interacted with other related texts in the Bible and other Church Fathers. The results of the analysis show that the plea for God's mercy in the prayer of Jesus makes people realize that God is the only source of help in physical and mental pain and suffering. Abstrak: Doa Yesus adalah doa berpusat sepenuhnya pada Nama-Nya dan mempunyai kuasa untuk mengusir setan. Namun penting untuk dipahami bahwa Doa Yesus bukan sekedar rumusan atau mantra, melainkan dialog suci antara individu dan Tuhan. Beberapa penafsiran dan praktik tentang Doa Yesus mungkin menyimpang dari ajaran Gereja, sehingga penting untuk membedakan bimbingan rohani yang benar. Doa Yesus bukanlah doa yang panjang atau berulang-ulang, melainkan ungkapan tulus dari keinginan seseorang akan belas kasihan, pengampunan, dan persatuan dengan Kristus. Doa Yesus berakar pada ayat-ayat Alkitab dan membutuhkan kerendahan hati, pertobatan, dan hubungan yang semakin intim dengan Kristus. Dalam mengamalkan Doa Yesus, penting untuk mengacu pada kebijaksanaan dan bimbingan para Bapa Suci dan mencari bimbingan dari ayah dan ibu rohani. Doa Yesus relevan di zaman sekarang dan dapat menjadi sumber kenyamanan, kekuatan, dan pertumbuhan rohani bagi mereka yang berupaya memulai perjalanan konsentrasi dan persekutuan mendalam dengan Tuhan Yesus Kristus. Metode penelitian adalah kajian literature secara kepustakaan (library reseach) dan studi literatur dari tradisi gereja tentang doa Yesus, khususnya berdasarkan tulisan dari St. Ignatius Brianchaninov yaitu On the Prayer of Jesus yang di interaksikan dengan teks lain yang berkaitan didalam Alkitab dan Bapa-bapa Gereja lainnya. Hasil analisis menunjukkan bahwa permohonan belas kasihan Allah dalam Doa puja Yesus menyadarkan manusia bahwa Allah satu-satunya sumber pertolongan dalam kesakitan dan penderitaan fisik maupun batin.